Assessment of the impact of digital technologies on the competitiveness of the retail market - M. A. Samokhin (Путеводитель предпринимателя, 2025)
The article examines the specifics of digital technologies in the context of the development of the trade industry, in particular retail. The emphasis is placed on the fact that in the context of digitalization, the retail market has undergone significant changes, having restructured its methods and approaches to new technological ways. The theoretical part of the paper describes different approaches to understanding the essence of competitiveness in the context of digitalization.   The purpose of the article is to conduct a comprehensive assessment of the impact of digital technologies on the competitiveness of the retail market.   In the current conditions of economic development and a large range of goods, it is difficult to maintain a decent level of competitiveness, which requires an in-depth analysis of new assessment methods.   The subject of the study is digital technologies that can significantly affect retail trade.   The methods used in the work include theoretical analysis, statistical method, quantitative methods, method of deduction and generalization of the obtained results. The results of the work emphasize the importance and role of digitalization tools such as artificial intelligence, big data, analytics, and the Internet of Things in the implementation of retail strategies. Modern enterprises should pay more attention to this aspect, as technology will help them improve the efficiency, competitiveness and adaptability of their operations.